The health risks of doping during the Cold War: A comparative analysis of the two sides of the Iron Curtain - Hunt, T. M.; Dimeo, P.; Hemme, F.; Mueller, A. (The International Journal of the History of Sport, 2014)
This article compares East Germany`s Cold War-era approach to doping to that of the USA`s in terms of their respective impacts on medical risk. Although deserving of criticism on many levels, the GDR doping programme featured a number of safeguards designed to minimise medical dangers. Unlike their East German counterparts, American governmental units were not direct y involved in the administration of performance-enhancing substances. The US approach to doping was not ideal in terms of medical risk, however. As a result of the country`s regulatory approach to doping, the country`s athletes frequently turned to black market sources for doping agents. It was also relatively common for American athletes to use performance-enhancing drugs without the benefit of medical supervision. The US approach to doping was in these ways inferior to that of East Germany`s on the subject of medical risk.